THE IMPACT OF CLIMATE CHANGE ON GLOBAL WATER RESOURCES: CHALLENGES AND SOLUTIONS - Sunita Devi (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The impact of climate change on the availability and quality of water on a worldwide scale is being more and more acknowledged as a serious danger to water supplies. A variety of factors, including changing precipitation patterns, increased frequency and severity of extreme weather events (such as floods and droughts), and overall warming of the planet, are influencing the availability, distribution, and use of freshwater. climate change’s complex effects on the world’s water supplies, including how shifting weather patterns influence water availability, water quality, and water resource management. As a result of these changes, problems including water contamination from extreme weather, strain on water infrastructure, and worsening water scarcity in dry places are becoming more common. possible approaches to lessen these effects, such as innovative water conservation and desalination technology, regulatory frameworks that encourage responsible water usage, and adaptive water management techniques. Also covered are the ways in which international collaboration and initiatives to reduce the effects of climate change might help with water-related issues. Urgent action is needed to guarantee water security in a changing climate. This article seeks to give a complete knowledge of the complicated relationship between climate change and water resources by recognising the issues and suggesting solutions.